2020
DOI: 10.32662/gjfr.v3i2.993
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Vegetasi Di Kawasan Pulau Menjangantaman Nasional Bali Barat (Tnbb)

Abstract: Pulau Menjanganmerupakan kawasan dalam Taman Nasional Bali Barat (TNBB) yang tergolong kawasan pelestarian alam yang memiliki vegetasi yang beragam, khususnya ekosistem darat dan ekosistem laut. Ekosistem darat terdiri hutan dataran rendah, savana, dan hutan pantai. Keberadaan vegetasi di Pulau Menjangansangat penting guna mendukung fungsi kawasan dalam pelestarian alam. Namun, data tentang vegetasi pada kawasan Pulau Menjanganmasih sangat terbatas. Oleh sebab itu perlu adanya penelitian tentang analisis veget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Menjangan Island has a variety of vegetation which is divided into lowland forest areas, savanna, and coastal forests. It can be concluded that Menjangan Island is the right habitat for the deer population (Rahayu et al, 2020). Therefore, because there are no observations regarding the social behavior of C. timorensis on Menjangan Island, this observation needs as an effort to conserve C. timorensis on Menjangan Island, West Bali National Park.…”
Section: Introductionmentioning
confidence: 97%
“…Menjangan Island has a variety of vegetation which is divided into lowland forest areas, savanna, and coastal forests. It can be concluded that Menjangan Island is the right habitat for the deer population (Rahayu et al, 2020). Therefore, because there are no observations regarding the social behavior of C. timorensis on Menjangan Island, this observation needs as an effort to conserve C. timorensis on Menjangan Island, West Bali National Park.…”
Section: Introductionmentioning
confidence: 97%